Design, synthesis and evaluation of novel substituted fused pyrido diazepine and pyrimido piperazine derivatives: In vitro cytotoxicity study over various cancer cell lines - Jignesh B. Timaniya; Paranjay H. Parikh; Mrugesh J. Patel; Gayatri Dave; Kaushal P. Patel (Results in Chemistry, 2023)
The current study describes, a novel combinatorial library of substituted fused pyrimido[3,2–e]pyrrolo[1,2-a]piperazine and pyrido[3,2-b]pyrrolo[1,2-d][1,4]diazepin heterocycles procured via utilization of suzuki coupling and acid amine coupling protocols. The synthesized compounds were screened for their in vitro cytotoxic activity over nine different cancer cell lines such as U-251, Panc-1, MCF-7, HepG2, DU-145, A549, 786-O, OVCAR3 and HCT-116 as well as on non-cancerous cell lines like normal human lung cell line WI38 and Mouse embryonic normal cell line NIH3T3 to evaluate safety profile of synthesized compounds. The bioassay results indicates that compound Cpd-J2 to be most potent among all the synthesized compounds towards ovary cancer cell lines (OVCAR-3) with promising activity value (EC50: 6.3 μM) relative to standard doxorubicin (EC50: 0.2 μM).